Quality Changes during Frozen Storage of Mechanical-Separated Flesh Obtained from an Underutilized Crustacean - Silvia Tappi; Ana Cristina De Aguiar Saldanha Pinheiro; Dario Mercatante; Gianfranco Picone; Francesca Soglia; Maria Teresa Rodriguez-Estrada; Massimiliano Petracci; Francesco Capozzi; Pietro Rocculi (Foods, 2020)
Despite their high nutritional value, high quantities of fish caught in the Adriatic Sea are underused or discarded for their insignificant economic value. Mechanical separation of flesh represents an opportunity for developing innovative semi-finished products, even if it can promote an increased quality degradation rate. The aim of this study was to evaluate physico-chemical modifications of mechanically separated mantis shrimp flesh during deep-freezing storage. Flesh samples obtained using a belt-drum separator, frozen and vacuum-packed, were stored at 3 temperatures (industrial: −26 °C; domestic: −18 °C and abuse: −10 °C) for 12 months. During storage, qualitative (color, water content, pH, fatty acids (FA) and lipid oxidation) were evaluated. Fish freshness parameters (e.g., trimethylamine (TMA), dimethylamine (DMA) and amino acids) were assessed using nuclear magnetic resonance (1H-NMR). The mechanical separation process accelerated the initial oxidation phenomena, promoting color alterations, compared to manual separation. The main degradation phenomena during storage were significantly affected by temperature and were related to changes in luminosity, oxidation of n-3 polyunsaturated fatty acids (PUFA), increased lipolysis with release of free FA, production of TMA and DMA by residual enzymatic activity, and changes in amino acids due to proteolysis. The inter-disciplinary approach permitted important findings to be made, in terms of the extent of different degradative phenomena, bound to processing and storage conditions of mechanically separated mantis flesh.